Jejuno-Ileal Atresia: Faktor-Faktor yang Mempengaruhi Mortalitas - Sugianto Prajitno; Ayu Anulus (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Jejuno-ileal atresia (JIA) is one of the leading causes of neonatal bowel obstruction. Over the last decade, mortality has decreased, with recent studies reporting a mortality rate of 11%. This study aimed to evaluate factors affecting mortality among patients with JIA. A retrospective cross-sectional study was conducted on all JIA patients admitted between January 2019 and December 2024. Demographic variables including gestational age (prematurity ≤36 weeks), birth weight (low birth weight/LBW ≤2,500 grams), sepsis, and location of atresia were analyzed in relation to mortality using Chi-square and logistic regression tests. Thirty neonates (15 boys and 15 girls) were included. Primary anastomosis was performed in 18 patients (60%), while 12 patients (40%) underwent stoma formation. The mean time to achieve full enteral feeding was 10.23 days (range 6–35 days). Mortality occurred in 17 of 30 patients (56.7%), of which 9 were premature, 11 were LBW, and 13 had sepsis. Jejunal atresia was found in 8 patients with 5 deaths, while ileal atresia was present in 22 patients with 12 deaths. Sepsis showed a significant association with mortality (p= 0.030), and combined LBW and prematurity were also significantly associated (p= 0.010). Multivariate analysis revealed that LBW and prematurity were independent predictors of mortality. In conclusion, while sepsis was significantly associated with mortality in univariate analysis, LBW and prematurity emerged as significant predictors in multivariate analysis.